Implementasi Algoritma Fuzzy Tsukamoto Pada Prototype Regulator Suhu Kandang Kelinci - Halim Agung; Claude Calvin Alsher (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
Many people are interested in caring for rabbits because they can be used as entertainment facilities by seeing the behavior of animals that can make their owners entertained because of the animals, but many people do not understand how to care for rabbits properly so that they cause illness and even death. To overcome this problem, a research was conducted to design a prototype that applies the Tsukamoto fuzzy algorithm to the rabbit cage prototype by measuring the temperature in the rabbit cage which is also influenced by the environment around the rabbit cage by using DH11 sensor. Based on the results of the study by testing 50 times, the DHT11 sensor can read the temperature in the rabbit cage by 60% level and error by 40%, due to weather and temperature changes that cannot be predicted